2022
DOI: 10.3991/ijoe.v18i10.31347
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Segmentation of Kidney Tumors Using Variants of U-Net Architecture

Abstract: Kidney Cancer is one of the most prevalent diseases that is more common in men than in women. Detecting kidney tumors at an early stage has been found to increase survival rates of patients. It is therefore important to accurately segment tumors in Computed Tomography(CT) images. To assist in early detection of kidney tumors in CT images, we present a method for segmenting kidney tumors using deep convolutional neural networks. Predicted models using U-Net and Attention U-Net architectures are ensemble for eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…The performance of this architecture outperformed U-Net by 10.15 percent, 5.0 percent, 2.6 percent, 1.4 percent, and 0.6 percent, respectively. TM G et al [24] utilized attention-based U-Net for segmentation of tumor. This model accomplished the ensemble by weighted averaging and showing promising results with an IOU score of 0.9591.…”
Section: Related Workmentioning
confidence: 99%
“…The performance of this architecture outperformed U-Net by 10.15 percent, 5.0 percent, 2.6 percent, 1.4 percent, and 0.6 percent, respectively. TM G et al [24] utilized attention-based U-Net for segmentation of tumor. This model accomplished the ensemble by weighted averaging and showing promising results with an IOU score of 0.9591.…”
Section: Related Workmentioning
confidence: 99%
“…The improvised model achieves a better MS lesion segmentation outcome than the standard CNN model [32,33]. In [28] showed that the UNET architecture are very good in performing segmentation of tumor in Kidney using CT images. However, tumor segmentation using brain MRI [29] is challenging due to presence of motion artifacts; thus, requires efficient preprocessing technique [30,31].…”
Section: 1mentioning
confidence: 99%